1992
DOI: 10.1136/bjsm.26.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Training-overtraining: performance, and hormone levels, after a defined increase in training volume versus intensity in experienced middle- and long-distance runners.

Abstract: Performance and hormones were determined in eight middle- and nine long-distance runners after an increase in training volume (ITV, February 1989) or intensity (ITI, February 1990). Seven runners participated in both studies. The objective was to cause an overtraining syndrome. The mean training volume of 85.9 km week-1 increased within 3 weeks to 176.6 km week-1 during ITV and 96-98% of training volume was performed as long-distance runs at mean(s.d.) 67(8)% of maximum capacity. Speed endurance, high-speed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
3
25

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 18 publications
4
101
3
25
Order By: Relevance
“…Além disso, Steinle [81] encontrou uma correlação negativa entre a excreção de catecolaminas e a latência da fase REM do sono (r=-0,46; p<0,01), confirmando a hipótese de que uma diminuição na excreção de catecolaminas pode indicar a presença de fadiga central. Com relação à concentração plasmática de catecolaminas, em atletas em overtraining, tem se observado um aumento nos níveis de noradrenalina plasmática em repouso e em resposta ao exercício de intensidade moderada [46,49]. Hooper et al [34] também verificaram aumento nas concentrações plasmáticas de noradrenalina no repouso, em nadadores em OT.…”
Section: ) Variações No Eixo Hipotálamo-hipófise-adrenal (Hha)unclassified
See 1 more Smart Citation
“…Além disso, Steinle [81] encontrou uma correlação negativa entre a excreção de catecolaminas e a latência da fase REM do sono (r=-0,46; p<0,01), confirmando a hipótese de que uma diminuição na excreção de catecolaminas pode indicar a presença de fadiga central. Com relação à concentração plasmática de catecolaminas, em atletas em overtraining, tem se observado um aumento nos níveis de noradrenalina plasmática em repouso e em resposta ao exercício de intensidade moderada [46,49]. Hooper et al [34] também verificaram aumento nas concentrações plasmáticas de noradrenalina no repouso, em nadadores em OT.…”
Section: ) Variações No Eixo Hipotálamo-hipófise-adrenal (Hha)unclassified
“…Por exemplo, Lehmann, Foster e Keul [48] concluíram que a implantação de um programa de treinamento diminuiu a sensibilidade da glândula adrenal ao ACTH em atletas recreacionais. Isto poderia explicar alguns estudos que indicaram uma diminuição na liberação do cortisol em atletas em OT [4,49,84].…”
Section: ) Variações No Eixo Hipotálamo-hipófise-adrenal (Hha)unclassified
“…Urinary catecholamines measured during resting periods have been reported to show lower levels after overtraining compared to levels prior to the overtraining (Lehmann et al, 1991). Venous norepinephrine may rise after workouts in short periods of resistance exercise (Fry, Kraemer & Van Borselen, 1994) or may decrease with exhaustion in endurance exercise (Lehmann, Gastmann & Petersen, 1992;Lehmann, Schnee, & Scheu, 1992).…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Research showed that this popular method heals post-exercise muscle damage. Although there is very few research, the studies conducted focused on postexercise muscle damage and showed different results in terms of its effectiveness [15,16].…”
Section: Electrostimulation and Core Exercises On Recovery Vol 6 (4)mentioning
confidence: 99%